An investigation of the evolutionary constraints and malleability of facilitated visual attention to threats - Freeman, Tyler E. (Kansas State University, 2012)
Öhman and Mineka (2001) proposed the existence of an evolved fear module with four Fodorian characteristics of modularity. They presented evidence that the fear module is selective, automatic, encapsulated, and operates in dedicated subcortical neural circuitry. The consistently rapid physiological and behavioral (attention capture) evidence (e.g., Öhman & Mineka, 2001) provides clear support for its automaticity. However, recent developments (e.g., Blanchette, 2006) cast doubt on the selectivity of the module. Specifically, it is unclear whether or not the fear module automatically responds selectively to evolutionarily ancient fear stimuli or whether modern threats may also elicit automatic responding. Furthermore, previous research using visual search paradigms has produced unclear results regarding the evolutionarily derived selectivity of the fear module. Unfortunately, the visual search method is notoriously sensitive to visual characteristics of stimuli (Duncan & Humphreys, 1989). However, eye movements provide a valid alternative measure of covert attention capture. In order to clarify the issues, Experiment 1 used an oculomotor inhibition paradigm to present ancient and modern threats with one another or neutral stimuli in competition for visual attention. In addition, we collected measures of participants’ experience with the stimuli to assess the influence of experience/familiarity/learning on rapid attention to threats. Furthermore, because image inversion maintains low level stimulus characteristics (e.g., spatial frequencies, contrast, and luminance) while disrupting the semantic processing of images, presenting the stimulus pairs upside down was used to determine whether any observed effects were due to low level stimulus characteristics. Experiment 1 produced null results with respect to systematic differences in attentional processes as a function of threat type. Because Experiment 1 was modeled after Nummenmaa et al., (2009, Exp 3), it was therefore necessary to attempt to replicate their findings. Experiment 2 successfully replicated the findings of Nummenmaa et al. Therefore, it is suggested that the rapid attention processes responsible for systematic deviations in saccade trajectories seen in Experiment 2 (and Nummenmaa et al., 2009, Exp 3) do not translate to the methodology used in Experiment 1. Given the findings from the present study, the question of whether or not there exists and evolved fear module remains open. This study clearly supports the existence of an attentional bias for emotional content as indicated through the use of oculomotor inhibition paradigm. However, like the visual search methodology, the oculomotor inhibition paradigm appears to be very sensitive to visual differences of the stimuli.
Keywords: Threat; Evolutionary Psychology; Attention; Oculomotor Inhibition; Psychology (0621)